Giant left anterior descending coronary artery (LAD) aneurysm - Altay, Servet; Velibey, Yalçın; Çakmak, Hüseyin Altuğ; Keleş, İbrahim and Kızılay, Mehmet and Erer, Betül (Cerrahpaşa Medical Journal, 2013)
A 45- year-old male patient admitted to our clinic with retrosternal chest pain radiating to left arm with a duration of 12 hours. Electrocardiography and transthoracic echocardiography were normal. Serum troponin I level was significantly high and therefore he was hospitalized with a diagnosis of acute coronary syndrome. The coronary anjiography showed serious multivessel coronary artery disease concomitant with fusiform type of giant coronary aneurysm in proximal segment of the left anterior descending artery (LAD). Therefore coronary artery bypass graft (CABG ) operation were performed. We present here a patient with giant LAD aneursym concomitant with obstructive atherosclerotic coronary artery disease. This is one of the largest LAD aneursym that was reported in the literature.